Challenges and controversies in the treatment of spinal tuberculosis. (May 2020) - Pandita, Aakriti; Madhuripan, Nikhil; Pandita, Saptak; Hurtado, Rocio M.
Abstract: Current guidelines regarding management of spinal TB are mostly extrapolated from trials on pulmonary disease. Since the British Medical Research Council (BMRC) trials in the 1970s, there are not many good quality studies that substantiate best practice guidelines for the management of this entity. Tuberculous infection of the spine behaves much differently from bacterial osteomyelitis and limited data leads to ambiguity in many cases. Although a few studies have been conducted in patients with spinal TB, most were in the era preceding short course chemotherapy and prior to current radiological and surgical advances. While spinal TB is primarily managed medically, surgical intervention may be needed in certain cases. We discuss areas of uncertainty and challenges that exist with regards to medical treatment, diagnosis, therapeutic endpoints, and a few surgical considerations. Substantial delay in diagnosis continues to be common with this disease even in the developed nations, leading to substantial morbidity. In light of limited evidence, there is an emerging recognition of the need to individualize various aspects of its treatment such as duration, frequency and acknowledging the limitations of various diagnostic and radiological modalities. We aim to consolidate potential areas of research in the diagnosis and management of spinal TB and to revisit the latest published evidence on its redressal.